Provenance and annotation of data and processes : 6th International Provenance and Annotation Workshop, IPAW 2016, McLean, VA, USA, June 7-8, 2016, proceedings /: 6th International Provenance and Annotation Workshop, IPAW 2016, McLean, VA, USA, June 7-8, 2016, proceedings. (2016) - Unknown
No abstract available